Compliance of Financial Statements of Islamic Banks of Pakistan with AAOIFI Guidelines in General Presentation and Disclosure - Asim Ehsan; Syed Kashif Saeed; Muhammad Asghar Shahzad; Hafiz Rauf Iqbal (SEISENSE (PRIVATE) LIMITED, 2019)
Objective - This study intends to investigate the extent of voluntary financial reporting compliance made by Islamic banks of Pakistan as suggested by Islamic accounting standards (i.e. AAOIFI). Design/Methodology - The study is based on an empirical evaluation of financial statements of Islamic banks of Pakistan. Data sample consists of financial statements for the years 2009, 2015, 2016 and 2017 relating to of all four full-fledged Islamic banks in Pakistan. The first standard in Islamic accounting standards suggests a total of 111 items for compliance while preparing a financial statement of Islamic Banks. As per existing regulatory requirements, Islamic banks in Pakistan are required to adopt International Financial Reporting Standards while preparing their financial statements. Findings - However, the analysis suggests Islamic banks in Pakistan are in compliance of more than 50% of requirements as suggested by Islamic accounting standards. Implications – The insights will help the industry decision makers to increase the voluntary disclosures by the Islamic banks.